Simulated training model of ureteropyelic anastomosis in laparoscopic pyeloplasty - Lima,Juliana Cynara Santos (2020)
Abstract Purpose: To develop a model for simulated training of ureteropyelic anastomosis in laparoscopicpyeloplasty. Methods: Longitudinal and experimental study, with 16 participants. A synthetic instrument was produced to simulate the renal pelvis and the proximal portion of the ureter positioned on a platform within laparoscopic simulators, thereby resulting in the realistic simulation of the ureteropelvic anastomosis. A step-by-step guide was also developed for the accomplishment of the ureteropelvic anastomosis training model. Results: In the evaluation of all participants’ suture training, a decrease was found in the time needed to perform the anastomosis, with a median of 17.83 min in the 1st step and 14.21 min in the last one (p = 0.01). Regarding the knots, in the 1st step, 5% of them were considered firm, with an evolution to 30% in the last step (p = 0.011). Conclusion: We noticed improvement in the ability to perform the ureteropelvic anastomosis by participants with no experience with it. Therefore, even unexperienced participants can improve their skills with this training. Moreover, we observed the effectiveness of the model use, confirmed by the participants’ opinion and its validation by expert surgeons.